Dairy Enterprise – 2,400 Lactating Cows (Freestall) - Dhuyvetter, Kevin C.; Harner III, Joseph P.; Brouk, Micheal (My University, 2012)
This publication describes the production costs and returns for a dairy enterprise with 2400 lactating cows in a freestall system.
MF2442_2012_01
Keywords: MF2442; Economics; Livestock; MF